Copy Number Alterations in Glioma Cell Lines - Meléndez, Bárbara; García-Claver, Ainoha; Ruano, Yolanda; Campos-Martín, Yolanda; Lope, Ángel Rodríguez de; Pérez-Magán, Elisa; Mur, Pilar; Torres, Sofía; Lorente, Mar; Velasco, Guillermo; Mollejo, Manuela (IntechOpen, 2011)
None